Assimilating new leaders : the key to executive retention - Downey, Diane (AMACOM, 2001)
"Since each new executive represents the future of an organization, it is important - in fact imperative - that the success of their relationship not be left to happenstance and luck. Assimilating New Leaders provides a step-by-step program for ensuring a new leader's ability to survive and thrive from his or her first day in an organization. In addition, it greatly enhances the organization's chances of fostering an orderly transition - and a successful, long-term relationship."--Jacket